Globalization and the developing countries [ emerging strategies for rural development and poverty alleviation - Bigman, David (CABICABI Publishing inassociation with the International Service for National Agricultural Research, 2002)
This book reviews the impact of globalization by examining, for example, how changes in global trading rules and regulations, the removal of trade barriers, and the elimination of many country-specific and commodity-specific agreements affect the economes of developing countries. In particular, it studies the effect of these factors on the agricultural sectors of these countries. Part I of the book (chapter 1) is a general background to the reviews of the experience of individual countries. It provides a survey of the debates over the benefits of globalization for developing countries and the merits of the development and trade strategies promoted by the World Bank and the IMF since the late 1960s. Part II (chapters 2-6) examines the effects of the changes in the global trading system and the impact of internal policy reforms in selected developing countries (China, India, Ghana, Kenya and Cameroon) on their economy and their agricultural sector. The reviews focus on the reforms implemented by these countries under their various structural adjustment programmes and their subsequent agreements as they joined the World Trade Organization (WTO). Part III (chapters 7-10) reviews the impact of a number of key changes in the rules, standards, and institutions that govern the global trading system under the WTO Agreements and their effect on the agricultural sector and on public agricultural research. The reviews cover the changes that followed the agreements on global standards for agricultural trade and intellectual property rights, the restructuring of the global trading system for many agricultural products in supply chains that are often dominated by multinational corporations, and the growing share of the private sector in agricultural research. Part IV (chapters 11-15) focuses more specifically on the necessary changes in the role and mode of operation of public agricultural research. The book has a subject index.